Comparison between support vector machine and deep learning, machine-learning technologies for detecting epiretinal membrane using 3D-OCT - Sonobe, Tomoaki; Tabuchi, Hitoshi; Ohsugi, Hideharu; Masumoto, Hiroki; Ishitobi, Naohumi; Morita, Shoji; Enno, Hiroki; Nagasato, Daisuke (International Ophthalmology, 2019)
Purpose In this study, we compared deep learning (DL) with support vector machine (SVM), both of which use three-dimensional optical coherence tomography (3D-OCT) images for detecting epiretinal membrane (ERM). Methods In total, 529 3D-OCT images from the Tsukazaki hospital ophthalmology database (184 non-ERM subjects and 205 ERM patients) were assessed; 80% of the images were divided for training, and 20% for test as follows: 423 training (non-ERM 245, ERM 178) and 106 test (non-ERM 59, ERM 47) images. Using the 423 training images, a model was created with deep convolutional neural network and SVM, and the test data were evaluated. Results The DL model’s sensitivity was 97.6% [95% confidence interval (CI), 87.7–99.9%] and specificity was 98.0% (95% CI, 89.7–99.9%), and the area under the curve (AUC) was 0.993 (95% CI, 0.993–0.994). In contrast, the SVM model’s sensitivity was 97.6% (95% CI, 87.7–99.9%), specificity was 94.2% (95% CI, 84.0–98.7%), and AUC was 0.988 (95% CI, 0.987–0.988). Conclusion DL model is better than SVM model in detecting ERM by using 3D-OCT images.